(untitled) (Research, Society and Development, 2022)
Pole Dance is a physical exercise that uses friction and opposition between the practitioner’s body and a vertical bar to perform plastic, static or dynamic figures and postures, with elements of gymnastics and circus acrobatics, composing dances or sequences. acrobatics. This research on Pole Dance aimed to carry out a systematic review of qualitative analysis of articles published in Portuguese, classifying them according to their theme. As a result, it was found that in the case of a sports practice, there are few studies developed in the country. In this study, eighteen studies were selected after a critical analysis, but only two of them were really focused on the hard area (a field of study that in turn encompasses disciplines such as physiology, biomechanics, kinesiology, anatomy, kinematics, among other scientific practices). It became clear that Pole Dance is a female domain practice and that more studies are needed to scientifically support the development of Pole Dance as a practice of physical exercise and sport.